METODE GURU DALAM MENANGANI ANAK BERKEBUTUHAN KHUSUS (AUTISME) DI SEKOLAH UMUM MI AL-MA`ARIF 02 SINGOSARI MALANG - Siti Humairoh; Ika Ratih Sulistiani; Zuhkhriyan Zakaria (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
The tittle of this thesis is “Teacher`s Method in Handling Children with Special Needs (AUTISME) in Public School MI Al-Ma`arif 02 Singosari Malang”. The research focus on: 1)How is the teacher`s method of dealing with students with special needs in public schools, 2) What are the results of the methods applied by teachers in dealing with children with special needs?, 3) What are the supporting and inhibiting fagtors for teachers?. The position of the researcher acts as an observer. This study used qualitative research methods. The results of the research obtained by researchers are the learning methods used by teachers in school still use learning methods in general there is no method specifically for children with special needs,teachers do not understand about learning methods for children with special needs, school also do not have special learning facilities for students especially those who study at the school, other students already understand the needs experienced by their classmates, the many lack of facilities owned by the school create many obstacles thet teachers get during teaching.